Dr. Elen De Masi — Deep Plane Facelift — Curitiba - De Masi, Elen (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Elen De Masi, practicing in Curitiba, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003255; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; curitiba